Staging Malay Hospitality Among Women’s Homestay Operators In Penang Island An Anthropological Perspectives - Aziz, Farah Syazwani Hayrol; Selamat, Nor Hafizah (Universiti sains malaysia, 2020)
Tourism has been considered as a big part of the hospitality industry. Hospitality refersto the relationship process between a guest and a host,and the act or practice of being hospitable. Anthropological literature considered hospitality like gift-giving which involves reciprocity, a negotiation between spontaneity and calculation, generosity and friendship. Although, it has been widely established that women have been the main player in hospitality industry particularly in rural tourism, little is known on the role of women in managing and staging of‘hospitality’. This study is to explore the managing and staging ‘Malay Hospitality’ by a group of women’s homestay operators on the Penang Island